2011
DOI: 10.2147/opth.s20033
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of spectral domain and time domain optical coherence tomography findings in toxoplasmic retinochoroiditis

Abstract: Purpose:To investigate spectral domain optical coherence tomography (SD-OCT) findings and compare them with time domain (TD)-OCT imaging of macula and retinochoroiditis lesions of patients with toxoplasmosis.Design:Prospective cross-sectional study.Methods:Ten eyes of 10 patients with active toxoplasmic retinochoroiditis were included. Morphologic features from the macula and retinochoroiditis lesions were obtained at baseline and at 6-week follow up. Scan acquisition protocols for TD-OCT included raster and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 12 publications
(8 reference statements)
3
26
1
Order By: Relevance
“…Increased retinal reflectivity and thickening of the lesion site [165,170,171] RPE -choriocapillaris/choroidal optical shadowing [165,170,171] Thickening of the posterior hyaloid, partial or complete posterior vitreous detachment over the retinochoroidal lesion [165,170,171] Multiple, small, granular hyperreflective spots on the vitreoretinal interface in the vicinity of the retinochoroidal lesion [166,168] Retinochoroidal scar…”
Section: Active Retinochoroidal Lesionmentioning
confidence: 99%
See 2 more Smart Citations
“…Increased retinal reflectivity and thickening of the lesion site [165,170,171] RPE -choriocapillaris/choroidal optical shadowing [165,170,171] Thickening of the posterior hyaloid, partial or complete posterior vitreous detachment over the retinochoroidal lesion [165,170,171] Multiple, small, granular hyperreflective spots on the vitreoretinal interface in the vicinity of the retinochoroidal lesion [166,168] Retinochoroidal scar…”
Section: Active Retinochoroidal Lesionmentioning
confidence: 99%
“…Decreased retinal thickness [165,171] Focal choriocapillaris/choroidal relative hyperreflectivity [165,171] Complete posterior vitreous detachment [165,171] Punctate outer retinal toxoplasmosis…”
Section: Active Retinochoroidal Lesionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a retrospective study of 926 patients with active ocular toxoplasmosis, 49 (5.0%) patients presented optic disc swelling, and this was most frequently found in association with an active distant focus of retinochoroiditis (11) . Macular serous retinal detachment and cystoid changes have also been described in patients with toxoplasmic retinochoroiditis not involving zone 1 (16,17) . Vitreous inflammation secondary to retinochoroiditis can also induce vitreous haze and di sorders of the vitreoretinal interface.…”
Section: Discussionmentioning
confidence: 93%
“…Diniz et al reported macular serous retinal detachment as the most common macular abnormality, with a ratio of 50% in patients with active toxoplasma chorioretinitis, and reported that one of their patients showed presence of residual fluid at follow-up visits [6]. The investigators stated that this could be related to the proximity of the lesion to the macula.…”
Section: Discussionmentioning
confidence: 98%